The Role of Several Compatibel Bacteria to increase the height accretion of Lycopersicon esculentum Mill. - Ernawati Ernawati; Linda Advinda (Serambi Biologi, 2020)
Fluorescent pseudomonads are biological agents that live in the soil around the roots which can increase plant growth. Compatible fluorescent pseudomonad is a combination of fluorescent pseudomonads, which aims to make the two bacteria function better in increasing plant growth. The aim of the study was to see the compatibility of several fluorescent pseudomonad isolates and to obtain the best fluooresen pseudomonad in improving the growth of tomato tannins (Lycopersiconesculentum Mill.). This study was an experimental study, using a randomized block design (RAD) with six treatments and three replications. The treatment is a combination of PfPb3 isolates with PfCas; a combination of PfCas isolates with LAHLS1 isolates; the combination of PfPj2 isolates with LAHLS1 isolates; combination of PfPj2 isolates with PfPj1 isolates; combination of PfPj2 isolates with LAHLS1 isolates and a combination of LAHLS1 isolates with PfKd7 isolates. The parameters observed were plant height. Data were analyzed using Analysis of Variance (ANOVA) test and not continued with DNMRT further test at the level of 5%. The results obtained by all compatible fluoreesene pseudomonad isolates can increase the height of tomato plants (Lycopersiconesculentum Mill.).